Strategi Kepala Sekolah untuk Meningkatkan Mutu Lulusan di SDN 25/1 Kampung Baru - Ade M Irqon; Nurul Marita; Wahyu Widyansih; Sani Samara (Lembag, 2025)
School principals have a strategic role in improving the quality of graduates at State Elementary Schools (SDN). This article reviews various strategies that school principals can implement to achieve these goals, including strengthening school-based management, developing curricula that are relevant to students' needs, and increasing the competence of teaching staff through professional training and coaching. Apart from that, optimizing facilities and infrastructure, applying technology in learning, and managing a conducive learning environment are also the main focus. School principals are also expected to be able to build collaboration with parents, the community and other stakeholders to create a supportive educational ecosystem. The results of this strategy are measured by improving student learning outcomes, strengthening character, and the readiness of graduates to continue their education to a higher level. This study confirms that the success of school principals' strategies is highly dependent on innovative and collaborative leadership abilities.